Peran Guru PAI Dalam Internalisasi Nilai Kejujuran Melalui Pembiasaan Karakter di MI Miftahul Huda Kedungcino - Muhammad Rifqi Alfariz; Alex Yusron Al Mufti (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2025)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in internalizing the value of honesty through character habituation at MI Miftahul Huda Kedungcino. Amid increasing moral challenges faced by students, character education-particularly the value of honesty-becomes essential in shaping individuals with integrity and social responsibility. Using a qualitative descriptive method, data were collected through interviews, observations, and documentation. The findings show that PAI teachers play a strategic role not only as educators but also as moral exemplars who integrate honesty into daily school routines and learning activities. Character habituation is implemented through structured religious activities such as dhuha and dhuhr prayers, recitation of Asmaul Husna, Aqidatul Awwam, and sholawat. These routines help students internalize honesty as part of their daily behavior. Supporting and inhibiting factors were also identified, including environmental influences, teacher commitment, and parental involvement. The study concludes that effective collaboration between schools, teachers, and families is vital in fostering honest and morally upright students in the digital era. The practical implication of this research is the need for teachers and madrasah policies to continuously strengthen character-based education through structured habituation programs, while future studies can expand the scope to other schools or explore digital-based strategies for character education.